Química mineral da clorita e muscovita hidrotermais do depósito aurífero X1, Província Aurífera de Alta Floresta (MT), Cráton Amazônico - Seebregts, Caio [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The Alta Floresta Gold Province (AFGP), central north region of the Mato Grosso State, corresponds to a crustal segment inserted in the southern sector of the Amazon Craton, approximately 500 km long and WNW-ESE direction. It consists of plutono-volcanic and volcano-sedimentary sequences of the Paleo-Mesoproterozoic, limited to the south by the Caiabis Graben, and to the north by the Cachimbo Graben. In the province, primary auriferous mineralizations total more than a hundred small deposits, and occur concentrated along the Peru-Trairão belt (NW-SE direction). In this context, primary mineralizations can be grouped into four main groups: (1) disseminated deposits of Au ± Cu; (2) Au ± Cu structurally controlled deposits; (3) disseminated deposits of Cu + Mo ± Au; and (4) Au + Pb + Zn ± Cu structurally controlled deposits. In these deposits, the phyllic alteration (muscovite + quartz + pyrite) and chlorite alteration (chlorite ± quartz) correspond to important recurrent hydrothermal typologies in the vast majority of deposits. The phyllic alteration, for example, represents the hydrothermal alteration temporarily related to the mineralized zones, whereas the chloritization usually represents a later hydrothermal stage and occur during the cooling of these magmatic-hydrothermal systems. In this scenario, although the main geological attributes of these deposits are relatively well equated, mineral chemistry studies are still scarce in the Province. The main goal of this study is the characterization of muscovite and chlorite variations from the phyllic and chloritc alteration stages, respectively, of the X1 deposit (Matupá, MT) through detailed petrographic studies and mineral chemistry analysis. The X1 deposit represents one of the most important intrusion-hosted gold systems of the province belonging to group (1). In this context, it was possible to characterize four distinct types of muscovite: (1) fibro-radial, (2) subeuedral, (3)...

A Província Aurífera de Alta Floresta (PAAF), centro-norte do Estado do Mato Grosso, corresponde a um segmento crustal inserido no setor sul do Cráton Amazônico, de aproximadamente 500 km de extensão e direção WNW-ESE. Constitui-se por sequências plutono-vulcânicas e vulcano-sedimentares do Paleo- ao Mesoproterozóico, limitadas a sul pelo Gráben dos Caiabis, e a norte pelo Gráben do Cachimbo. Na província, as mineralizações auríferas primárias totalizam mais de uma centena de depósitos de pequeno porte, e ocorrem concentradas ao longo do alinhamento Peru-Trairão de direção NW-SE. Neste contexto, as mineralizações primárias podem ser agrupadas em quatro grupos principais: (1) depósitos disseminados de Au ± Cu; (2) depósitos filonares de Au ± Cu; (3) depósitos disseminados de Cu + Mo ± Au; e (4) depósitos filonares de Au + Pb + Zn ± Cu. Nesses depósitos, as alterações fílica (muscovita + quartzo + pirita) e clorítica (clorita ± quartzo) correspondem a importantes tipologias hidrotermais recorrente na grande maioria dos depósitos. A alteração fílica, por exemplo, representa a alteração temporalmente relacionada às zonas mineralizadas, enquanto a cloritização usualmente representa os estágios mais tardios e frios do sistema magmático-hidrotermal. Neste cenário, embora os principais atributos geológicos dos referidos depósitos estejam relativamente bem equacionados, estudos de química mineral ainda são escassos na província. Deste modo, este trabalho tem por temática o estudo de química mineral da muscovita e clorita do depósito X1 (município de Matupá, MT), um dos principais sistemas magmático-hidrotermal e pertencente a primeira classe de depósitos. Para tal, esse trabalho se utilizou essencialmente de petrografia e microssonda eletrônica de setores representativos das alterações fílica e clorítica. Neste escopo, foi possível caracterizar quatro distintas tipologias de muscovita...
Keywords: Quimica mineralogica; Depositos hidrotermais; Ouro - Minas e mineração; Crátons; Mineralogia; Geoquímica; Alta Floresta (MT)